Non-tumor necrosis factor-based biologic therapies for rheumatoid arthritis: present, future, and insights into pathogenesis. - Paula, F (2014)
Therapeutic options for patients suffering from the more severe forms of spondyloarthritis have been rather limited in the last decades. There is now accumulating evidence that antitumor necrosis factor therapy is highly effective in spondyloarthritis, especially in ankylosing spondylitis and psoriatic arthritis. Based on the data recently published on more than 500 patients with ankylosing spondylitis and psoriatic arthritis, this treatment seems to be even more effective than in rheumatoid arthritis. The antitumor necrosis factor-alpha agents currently available, infliximab (Remicade), etanercept (Enbrel), and adalimumab (Humira), are approved for the treatment of rheumatoid arthritis in the United States and partly in Europe. The situation in spondyloarthritis is different from that of rheumatoid arthritis because there is an unmet medical need, especially in ankylosing spondylitis: no therapies with disease-modifying antirheumatic drugs are available for severely affected patients, especially with spinal disease. Thus, tumor necrosis factor blockers may even be considered a first-line treatment in a patient with active ankylosing spondylitis and psoriatic arthritis whose condition is not sufficiently controlled with nonsteroidal antiinflammatory drugs in the case of axial disease, and sulfasalazine or methotrexate in the case of peripheral arthritis. For infliximab, a dose of 5 mg/kg was required, and intervals between 6 and 12 weeks were necessary to suppress disease activity constantly-also a major aim for long-term treatment. The standard dosage of etanercept is 2 x 25 mg subcutaneously per week. There are no studies yet on adalimumab (standard rheumatoid arthritis dose, 20-40 mg subcutaneously every 1-2 weeks) in spondyloarthritis. Infliximab was very recently approved for AS in Europe. The efficacy of etanercept was first demonstrated in psoriatic arthritis, and it is now approved for this indication. A double-blind study has also been performed in ankylosing spondylitis, with similarly clear efficacy. There is preliminary evidence that both agents do also work in other spondyloarthritis, such as undifferentiated spondyloarthritis. Ideally, both agents will be approved soon for the short-term treatment of severe, uncontrolled spondyloarthritis. In parallel, studies should be performed to document the long-term efficacy of this treatment. There is hope that ankylosis may be preventable, but it remains to be shown whether patients benefit from long-term antitumor necrosis factor therapy and whether radiologic progression and ankylosis can be stopped. Severe adverse events have remained rare. Complicated infections including tuberculosis have been reported. These can be largely prevented by appropriate screening. At it stands now, the benefits of antitumor necrosis factor therapy in ankylosing spondylitis seem to outweigh these shortcomings.